Dehumanization, Fragmentation, and Trauma of Identity in Frankenstein in Baghdad by Ahmed Saadawi (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Benefitting from Frantz Fanon's theories, the present research analyzes how Ahmed Saadawi's Frankenstein in Baghdad represents the internalization of violence undergone by the colonized, where the brawl for justice is linked with feelings of anger, muddle, and anguish. At the core of this novel lies Shesma, a surreal figure, a stitched-together corpse that exemplifies the disjointed identity and cooperative trauma of a country struggling with the consequences of war and colonialism. This study maintains that Shesma is regarded not only as a real symbol of the bodily and mental wounds left by foreign occupation but also as a deep criticism of the cyclic spirit of violence in postcolonial societies. Shesma's body functions as a multifarious spot of confrontation and recovery due to typifying the dichotomy of the colonized subject's experience, struggling for freedom while concurrently dealing with the lingering threats of trauma. Moreover, this article inspects the themes of physical revulsion and phantom justice that pervade the novel, enlightening how Saadawi creates a story that disapproves of the basic grounds of radical violence. Saadawi also asks his readers to challenge the ethical uncertainties and moral predicaments encountered by people in a society where violence has become regularized and where the search for identity is tense with disintegration. By placing Frankenstein in Baghdad in the framework of Fanon's work, this study shows the close association between trauma, identity, and the sociopolitical situation of contemporary Iraq. Eventually, it contends that Saadawi not only blames colonialism and the constant violence that originates from it but also ratifies the Fanonian contradiction, demonstrating how the fight for freedom can be both a base of authorization and a foundation of suffering. Thus, this paper leads to a better understanding of the intricacies of postcolonial identity and the permanent influence of trauma in a world full of fight and displacement.